Diversity and population dynamics of estuarine fishes and crustaceans in Marudu Bay, Malaysia - Mohd Khatib, Mohd Azim (2014)
A study was conducted on fish composition, spatio-temporal distribution, catch-perunit- effort (CPUE), species diversity index and population dynamics of selected fishes and crustaceans from the estuarine area of Marudu Bay, Sabah, Malaysia from October 2012 to September 2013. There were five sampling stations (St1 - N 06º 36.169’ E 116º 46.400’, St2 - N 06º 36.651’ E 116º 48.895’, St3 - N 06º 36.700’ E 116º 47.775’, St4 - N 06º 36.751’ E 116º 47.816’ and St5 - N 06º 37.502’ E 116º 47.775’) for the study. Each sampling station was approximately 1 km apart from each other. Fish samples were collected by using gill nets. In total, 40 species of fish belonging to 29 families were identified from the estuarine waters of Marudu Bay, Sabah, Malaysia. Among them, 31 species occurred at St1 and St2, 26 species at St3, 25 species at St4 and 29 species at St5. Five species (Sardinella melanura, Gerres oyena, Leiognathus equulus, Atule mate and Sillago sihama) were the most dominant in the investigated areas. The higher total mean catch-per-unit-effort (CPUE) were observed at St1 (13.70 kg/net/hr) and St2 (13.30 kg/net/hr) which were just 1 and 2 km away from the river mouth, respectively, while lower total CPUE were found at St3 (2.51 kg/net/hr), St4 (1.61 kg/net/hr) and St5 (1.31 kg/net/hr) which were approximately 3, 4 and 5 km away from the river mouth, respectively. The Shannon- Wiener index was significantly higher in the monsoon seasons peaking in the months of January - February and June – August 2013. None of the diversity indices were significant among stations, with the exception of evenness, which was significantly (p < 0.05) higher at St3 than St2. The family richness results clearly indicated two peaks in a year; one peak was in December - March and another in August. The abundance of 10 species was found to be correlated (positive or negative) with the water parameters. The highest and significant regression coefficient was observed for Pseudorhombus cinnamoneus which indicated that 29% of their abundance was influenced by the major water parameters and the remaining 71% by other factors. The growth, mortality, recruitment and relative yield per recruit of the five selected dominant fish species (Rastrelliger kanagurta, Gerres oyena, Atule mate, Sillago sihama and Sardinella brachysoma) from Marudu Bay were investigated based on monthly length-frequency data, using FiSAT software. In terms of length-weight relationships, G. oyena, S. sihama and S. brachysoma showed a negative allometric nature of growth while R. kanagurta and A. mate showed a positive allometric nature of growth in the estuarine waters of Marudu Bay. For the record, only G. oyena had a continuous recruitment pattern with only one major cohort produced per year while the other four other species (R. kanagurta, A. mate, S. sihama and S. brachysoma) showed two major recruitment events per year indicating two cohorts were produced in a year. Results from the analysis of the exploitation rate (E) based on the fishing mortality estimates, indicate that the fishery of the selected five dominant fish species in Marudu Bay are below the optimum level of exploitation. This implies that the fish stocks in Marudu Bay are still abundant but any further unrestrained increase in fishing effort in the future might drive the fish stocks down and leads to economic losses.